Level of computer literacy among accounting lecturers in Universiti Teknologi MARA at Shah Alam and Jengka / Norlaila Mohd Din - Mohd Din, Norlaila (2001)
This study compares and contrasts the level ofliteracy among accounting lecturers between Shah Alam and Jengka Campuses and its relationship with management support and computer training program. This study is to gather information about the level of computer knowledge among accounting lecturers in the two campuses and their perception on computer training program and management support. The objective of the study are ; to compare the level of computer literacy among accounting lecturers between the two campuses ; to determine the relationship between (he level of computer literacy and the computer training ; and to determine the relationship between the level of computer literacy and management support. The study was conducted by distributing questionnaires to accounting lecturers in Accounting Faculty at Universiti Teknologi Mara in Shah Aiam and Jengka It is found that the level of computer literacy among accounting lecturers is at adequate level and no difference between the two campuses. Inconsistent with previous studies, the studies suggest that there is no the relationship between the level of computer literacy and the computer training. The study also found that there is significant relationship between the level of computer literacy and management support. This study provides a description and comparison of the level of computer literacy among accounting lecturers between Shah Alam and Jengka Campuses. The study also suggests that the management should give more support in order to improve the level of literacy among accounting lecturers such as providing enough facilities and Internet connection.